Pengaruh intensitas penggunaan aplikasi shopee terhadap perilaku konsumtif ditinjau dari persfektif Pancasila - Yani, Dwi Fitri; Salam, M.; Candra, Alif Aditya (Academy of Education Journal, 2024)
The development of globalization in the previously traditional economic sector has shifted towards digitalization, affecting the high use of the Shopee application by Jambi University PPKn students. This phenomenon has resulted in consumptive behavior that is not in harmony with the values of Pancasila. This study aims to determine the impact of the intensity of using the Shopee application on student consumptive behavior, by considering the Pancasila perspective. A quantitative approach was used in this study through survey methods, involving 39 respondents. Data analysis using SPSS Version 26 shows that the intensity of using the Shopee application significantly affects the consumptive behavior of Jambi University PPKn students, with a p-value of < alpha (0.000 < 0.05). The effect reached 54.3%, while other influencing factors were not studied in this study.